2021
DOI: 10.1002/humu.24187
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of pathogenic variants and founder effects in amelogenesis imperfecta associated with MMP20

Abstract: Amelogenesis imperfecta (AI) describes a heterogeneous group of developmental enamel defects that typically have Mendelian inheritance. Exome sequencing of 10 families with recessive hypomaturation AI revealed four novel and one known variants in the matrix metallopeptidase 20 (MMP20) gene that were predicted to be pathogenic. MMP20 encodes a protease that cleaves the developing extracellular enamel matrix and is necessary for normal enamel crystal growth during amelogenesis. New homozygous missense changes we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…As KLK4 and MMP20 seem to work in a collaborative manner, it is not surprising to note a similar dental phenotype in individuals with KLK4 (Hart et al, 2004) or MMP20 (Kim et al, 2005b) variants. We found 16 individuals (Supplementary Table S3; Supplementary Figure S2K) presenting with hypomature AI both in their primary and permanent dentitions; their phenotypes are similar to the ones described in the literature and associated with MMP20 recessive inheritance (Kim et al, 2005b;Ozdemir et al, 2005b;Papagerakis et al, 2008;Lee et al, 2010;Gasse et al, 2013;Kim et al, 2017;Wang et al, 2020;Nikolopoulos et al, 2021). Individuals 11.1,11.2,11.3 and 11.4 have compound heterozygous variants in MMP20 gene (Supplementary Figures S3.20,3.21,3.22).…”
Section: Mmp20supporting
confidence: 76%
“…As KLK4 and MMP20 seem to work in a collaborative manner, it is not surprising to note a similar dental phenotype in individuals with KLK4 (Hart et al, 2004) or MMP20 (Kim et al, 2005b) variants. We found 16 individuals (Supplementary Table S3; Supplementary Figure S2K) presenting with hypomature AI both in their primary and permanent dentitions; their phenotypes are similar to the ones described in the literature and associated with MMP20 recessive inheritance (Kim et al, 2005b;Ozdemir et al, 2005b;Papagerakis et al, 2008;Lee et al, 2010;Gasse et al, 2013;Kim et al, 2017;Wang et al, 2020;Nikolopoulos et al, 2021). Individuals 11.1,11.2,11.3 and 11.4 have compound heterozygous variants in MMP20 gene (Supplementary Figures S3.20,3.21,3.22).…”
Section: Mmp20supporting
confidence: 76%
“…The younger brother was heterozygous for the LAMA3 variant but inherited no MMP20 mutations. These 2 MMP20 mutations have never been reported in AI kindreds, bringing the number of known pathogenic MMP20 variants to 24 (Nikolopoulos et al, 2021; Wang et al, 2020). Phenotypically, it has been demonstrated that biallelic MMP20 mutations can cause a wide spectrum of enamel malformations, ranging from hypoplastic to hypomaturation defects (Wang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The younger brother was heterozygous for the LAMA3 variant but inherited no MMP20 mutations. These 2 MMP20 mutations have never been reported in AI kindreds, bringing the number of known pathogenic MMP20 variants to 24 (Nikolopoulos et al, 2021;Wang et al, 2020).…”
Section: Family 4 (Ng_0078532:g265216g > C)mentioning
confidence: 99%
“…Mutations in the gene encoding MMP-20 have been proven to cause disorders in proper enamel development such as amelogenesis imperfecta. The enamel of patients with this disorder is characterized by a soft and rough surface with foci of pigmentation [ 65 , 66 ]. Additionally, such patients are at risk of more rapid dental caries and earlier tooth loss [ 67 ].…”
Section: Metalloproteinases and Their Role In The Human Body With Spe...mentioning
confidence: 99%